Decomposição dos fatores de crescimento pró pobre: Evidências para a zona rural brasileira - Freitas, George Alberto de (2008)
Long-term economic growth is a sine qua non condition for ensuring the well being of a population and of their future generations. Must of the time the level of income of a given economy is insufficient to provide a decent life for the population in such a way to enable that everyone is included in the society of consumption. Though, as in Brazil's case, the income generated is more than enough to provide those benefits for the population, its distribution in fact, doesn't favor this desired outcome. Thus studies that attempts to anlyses the relation of income distribution and poverty are relevant. This paper analyses the factors of growth through the decomposition of poverty rates (proportion of poor, the poverty gap and quadratic gap poverty), in order to identify the posssible influence of economic growth and inequality of income distribution in the poverty indices. Additionally it analyses the evolution of the poverty indices as well its evolution in the period of 1995 and 2005 ased on data provided by the National Survey of Hoousehold (PNAD) at constan values corrected by the National Index od Consumer Price to 2005. Through this evolution it is possible to identify if economic growth is in favor or not of the poor. This model of decomposition allows for the separation of effects of economic growth and income distribution on the poverty indices. To achieve this result data on household per capita income of rural area and on the Lorenz curve are necessary. This two set of information give a measure of inequality. The analysis was made at the national, regional and state levels, and involve3d twenty states. The Federal District and the states of the north region, except Tocantins were excluded. The results indicate the occurrence of positive effects in relation to the poor for the Brazilian rural area in the majority of states. It also indicates that the Northeast region was the most affected with the phenomenon of rural poverty. The Northeast and the Northern regions are the ones where the proportions of poor were less reduced suggesting the formation of clubs of convergence. Al the state level it is important to note that the states of the South and Center-West regions are the leaders in reducing the rural poverty for all observed indices. These results can give a basts for implementation of strategies for public policies aimed at increasing regional economic activity, as well as policies for the distribution of income.